Management of Patients with Synchronous Liver Colorectal Cancer Metastasis - Sidorova, Aleksandra; Melekhina, Olga; Bashankaev, Badma (Digestive Disease Interventions, 2023)
Half of patients with colorectal cancer face liver metastasis. Tactically different approaches to the treatment of hepatic metastases, including using minimally invasive surgical techniques, have proven their effectiveness in improving oncological results. The correct choice of surgical treatment method depending on the number, localization, size of metastases, and their response to chemotherapy plays a crucial role in the further risks of disease progression. Liver resection is the standard of surgical treatment. If for some reason it is impossible to perform it, then the choice of the method of surgical treatment is performed among various methods of ablation and radiation therapy. The possibilities of intra-arterial chemotherapy, chemoembolization, and radioembolization are realized with chemoresistance and unresectability of foci for all types of surgery.
Keywords: colorectal cancer; liver metastasis; synchronous metastasis